2000
DOI: 10.1139/f99-288
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance, growth, and habitat use of age-0 steelhead (Oncorhynchus mykiss) grown in enriched and conventional hatchery rearing environments

Abstract: This study investigated whether culturing age-0 steelhead (Oncorhynchus mykiss) in habitat-enriched rearing tanks, containing a combination of in-water structure, underwater feeders, and overhead cover, affected competitive ability and habitat use compared with juveniles cultured in more conventional vessels. In laboratory tests, steelhead juveniles grown in the enriched tanks socially dominated size-matched competitors grown in conventional tanks. When both treatments were introduced into separate sections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 33 publications
2
128
2
Order By: Relevance
“…These results are similar to Brockmark et al [9], who found no significant difference in fish rearing performance with the addition of plastic plants and rocks to tank bottoms. Although neither this study nor Brockmark et al [9] found significant benefit with the use of environmental enrichment, benefits from the addition of structure in tanks has been found in other studies [2,6]. One difference that could account for the significant results of Kientz and Barnes [6] is the placement of structure in the tank.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…These results are similar to Brockmark et al [9], who found no significant difference in fish rearing performance with the addition of plastic plants and rocks to tank bottoms. Although neither this study nor Brockmark et al [9] found significant benefit with the use of environmental enrichment, benefits from the addition of structure in tanks has been found in other studies [2,6]. One difference that could account for the significant results of Kientz and Barnes [6] is the placement of structure in the tank.…”
Section: Discussioncontrasting
confidence: 68%
“…The use of environmental enrichment can be beneficial during salmonid rearing [2,6], but not all enrichment techniques are equally effective in improving fish rearing performance. The use of concrete blocks on tank floors as a method of enrichment is not recommended because of a lack of significant effect on fish growth, as well as increased demands on routine cleaning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has shown that the development of various fish behaviours are influenced by the experience of environmental complexity , Braithwaite 2006. Berejikian et al (2000Berejikian et al ( , 2001 have reported that rainbow trout Oncorhynchus mykiss reared in enriched environments were socially dominant to size-matched fish reared in plain environments. In juvenile Atlantic cod Gadus morhua, experience with spatial structures in the nursery environment increased behavioural flexibility , Salvanes et al 2007).…”
Section: Introductionmentioning
confidence: 99%